Cultural Adaptation In Literary Translation: An Analysis Of The Novels - Siregar, Ayunda Putri Amirah; Surayya, Azizah (PT. Kreasi Karya Majakata, 2023)
Translation is a timeless practice that facilitates communication between diverse linguistic and cultural communities. With the increasing global interaction, it becomes imperative for translators to not only decipher words but also comprehend the underlying cultural beliefs, values, and norms. This paper delves into the intricacies of literary translation, emphasizing the importance of preserving the emotional and psychological impact of the original text for the target language reader. To achieve this, translators often employ adaptation techniques to harmonize cultural elements from the source language into the target language, ensuring familiarity and resonance with the intended audience. This research focuses on the novel